Hospitalization Patterns for Inpatient Pediatric Surgery and Procedures in California: 2000–2016. (October 2020) - Muffly, Matthew K.; Honkanen, Anita; Scheinker, David; Wang, Tammy Nai-Yen; Saynina, Olga; Singleton, Mark A.; Wang, C. Jason; Sanders, Lee
Abstract : BACKGROUND: We report hospitalization patterns from 2000 to 2016 for young children (ages 0–5 years old) in California who underwent 1 of the 20 most common inpatient procedures that required general anesthesia and evaluate the estimated probability of treatment at a tertiary care children's hospital (CH) by year. METHODS: We hypothesized that children ⩽5 years old increasingly undergo care at tertiary care CHs for common inpatient surgeries or other procedures that require general anesthesia. Data from the California Office of Statewide Health Planning and Development dataset were used to determine procedure, patient age, year of procedure, and hospital name. Hospitals were designated as either tertiary care CHs, children's units within general hospitals (CUGHs), or general hospitals (GHs) based on the California Children's Services Provider List. A tertiary care CH was defined using the California Children's Services definition as a referral hospital that provides comprehensive, multidisciplinary, regionalized pediatric care to children from birth up to 21 years of age with a full range of medical and surgical care for severely ill children. We report the unadjusted percentage of patients treated at each hospital type and, after controlling for patient covariates and comorbidities, the estimated probability of undergoing care at a tertiary care CH from 2000 to 2016. RESULTS: There were 172, 318 treatment episodes from 2000 to 2016. The estimated probability of undergoing care at a tertiary care CH increased from 63.4% (95% confidence interval [CI], 62.4%–64.4%) in 2000 to 78.3% (95% CI, 77.3%–79.4%) in 2016. CONCLUSIONS: Children ⩽5 years old undergoing common inpatient procedures that require general anesthesia increasingly receive care at tertiary care CHs in California.